2021
DOI: 10.31389/jltc.56
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Evidence on the Use and Effectiveness of Decision Aids in Adult Social Care

Abstract: Context: Social care-related decisions can be complex but despite their widespread use in health care to help patients make similarly complex decisions, the use of decision aids in social care is not well examined. Objective: To review the international research evidence on decision aids in adult social care and investigate the availability of such aids for planning later life care on adult social care-related websites in England. Methods: Decision aid was defined broadly. Systematic searches for empirical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Other research could helpfully move from research on experiences and preferences to actual design and testing of support systems to improve navigation. A review of decision-making aids [21] has found a clear gap in research to support social care navigation, despite a plethora of such systems available in healthcare decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research could helpfully move from research on experiences and preferences to actual design and testing of support systems to improve navigation. A review of decision-making aids [21] has found a clear gap in research to support social care navigation, despite a plethora of such systems available in healthcare decisions.…”
Section: Discussionmentioning
confidence: 99%
“…While information alone may be regarded as necessary, it is unlikely to be sufcient to fully meet the criteria for good decision-making. A review of the skills needed to fnd and plan social care implies an almost inevitability that this could not be done without support [21].…”
Section: Introductionmentioning
confidence: 99%
“…When creating these aids, it is essential to consider 3 critical components, economic costs, health and recovery aspects, and social and environmental support. Despite the increasing availability of technology-based decision-making aids, printed materials in large print, colorful chart cards, or brochures remain the most widely accepted format among patients and their surrogates, especially for more elderly populations [ 25 ].…”
Section: Solution Strategies For This Clinical Scenariomentioning
confidence: 99%